2013
DOI: 10.1002/cctc.201300559
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Activation and Catalysis Driven by Iridium Complexes

Abstract: Recent reports on homogeneous catalytic transformation of carbon dioxide by iridium complexes have prompted us to review the area. Progress on new iridium catalysts for carbon dioxide transformations should take into account the interaction of carbon dioxide with the iridium center, which seems to be governed by the oxidation state of iridium and the nature of the carbon dioxide molecule. Most examples of iridium catalyzed carbon dioxide reductions are based on IrIII centers. These reactions take place through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 112 publications
0
32
0
Order By: Relevance
“…A significant intensity decrease of these peaks was observed in the spectrum of the used catalyst, suggesting the substantial loss of Cl − anions from the catalyst. On the basis of experimental and theoretical studies on previously reported reaction mechanisms of metal complexes, we propose a plausible reaction pathway for the CO 2 hydrogenation over the Ir‐PN‐PEI@TNT catalyst (Scheme ). In the initial stage of reaction, Cl − anion bonded to Ir III center is displaced by hydride (H − ) to create Ir‐trihydride as the real active species, in which basic amino groups on PEI assist the heterolytic dissociation of the adsorbed H 2 in the vicinity of the Ir center (Step 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant intensity decrease of these peaks was observed in the spectrum of the used catalyst, suggesting the substantial loss of Cl − anions from the catalyst. On the basis of experimental and theoretical studies on previously reported reaction mechanisms of metal complexes, we propose a plausible reaction pathway for the CO 2 hydrogenation over the Ir‐PN‐PEI@TNT catalyst (Scheme ). In the initial stage of reaction, Cl − anion bonded to Ir III center is displaced by hydride (H − ) to create Ir‐trihydride as the real active species, in which basic amino groups on PEI assist the heterolytic dissociation of the adsorbed H 2 in the vicinity of the Ir center (Step 1).…”
Section: Resultsmentioning
confidence: 99%
“…Since the direct CO 2 hydrogenation is thermodynamically unfavorable (Δ G ° 298 =+32.9 kJ mol −1 ), this process is commonly performed in the presence of homogeneous bases (NaOH and NEt 3 ) to shift the reaction equilibrium, yielding formate salts as products . Among the catalysts employed for catalytic hydrogenation of CO 2 to FA, homogeneous transition metal complexes have demonstrated to be efficient catalytic systems . For instance, the strong electron‐donating ability of phosphine‐ or nitrogen‐containing ligands in Ir III complexes with PNP pincer‐type ligands or N ‐heterocyclic ligands facilitates hydrogenation of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The pathway through which the decarboxylation reaction takes place is unclear, since this Ru center is coordinatively saturated. Two possible intermediates were proposed by the authors (Scheme ),[14b] the most likely being the CO 2 bridging species, because, first, similar complexes have been isolated and, second, the unsupported terminal coordination mode for CO 2 seems less likely . For the formation of this intermediate, the authors postulated a transient dissociation of the formate ligand followed by hydride abstraction – due to the lack of the vacant coordination site necessary for the β‐hydride elimination reaction to occur.…”
Section: Early Catalytic Systemsmentioning
confidence: 99%
“…The formation of formic acid is especially interesting because this molecule could serve as a hydrogen‐storage compound for fuel cells 10. A large number of transition‐metal‐based procedures1ce, 3a, 4b, d, 5c, e, 6c, e, 11 has been developed that include numerous iridium‐based catalysts1f for the homogeneous hydrogenation10a, c, 12 and electrocatalytic reduction6f, h, 13 of CO 2 . The mechanisms of the hydrogenation and electrocatalytic reduction systems are closely related and are based on the reaction of CO 2 with an iridium–hydride intermediate as a key step, which can occur either by the insertion of CO 2 into a MH bond11c, g, 12a, d or by hydride transfer from the metal center to a coordinated or non‐coordinated CO 2 molecule 11d.…”
Section: Introductionmentioning
confidence: 99%